The impact of ethical leadership on organizational citizenship behaviors: Moderating role of organizational cynicism - Mohamed Ahmed Ali Nemr; Yuhuan Liu (Cogent Business & Management, 2021)
The aim of this study was to test the relationship between ethical leadership (EL) and organizational citizenship behaviors (OCB) and to test the moderating role of organizational cynicism (OC) in this relationship. This study was conducted on a stratified random sample consisting of 400 faculty members and their assistants at the Sohag University in Egypt. We relied on the survey for data collection and were analyzed using simple regression, hierarchical regression moderated analysis (HRMA) and simple slope analysis. Results indicate that ethical leadership has a direct and indirect effect on organizational citizenship behaviors and Organizational cynicism modifies the relationship between ethical leadership and organizational citizenship behaviors so that the relationship is weaker among employees with a high level of cynicism in contrast to those with a low level of cynicism. Finally, we offer several conclusions concerning EL, OCB and OC.
Keywords: 650; ethical leadership; organizational citizenship behaviors; organizational cynicism